IDENTIFIKASI, EVALUASI DAN REKOMENDASI LAYANAN LUMPUR TINJA DI KOTA BANJARBARU KALIMANTAN SELATAN - Maimunah, Maimunah; Mahreda, Emmy Sri; Prihatini, Nopi Stiyati; Mahmud, Mahmud (EnviroScienteae, 2023)
The feces waste treatment installation (IPLT) pond capacity of Banjarbaru is 20 M3/ day, while the maximum amount per month in 2022 is only 11 M3 of household fecal waste that goes into IPLT. This shows that the excrement that enters the IPLT is below the IPLT capacity of Banjarbaru because currently, the sludge service has yet to be scheduled and is still using the on-call system. Meanwhile, Banjarbaru Regional Regulation No. 1 of 2021 regarding scheduled sludge services in Banjarbaru already exists. This study aims to identify and evaluate the existing conditions of the sludge service in Banjarbaru and develop recommendations for improving the sludge service in Banjarbaru. The method used in this research is a descriptive method using a questionnaire and conducting interviews with people who have used sludge services in 2022. Calculation of the results of the questionnaire uses a Likert scale, validity, and reliability tests. The results of the identification through the questionnaire revealed that the IPLT had been actively carried out with the on-call system; if implementing the scheduled feces sludge service (LLTT), several processes had to be improved, and the results of the evaluation stated that the community did not agree with the fees charged for the LLTT. Recommendations for sludge services are increasing the number of fleets, promoting sludge services, and improving the administration system.